STUDY ON THE QUALITY AND SELF LIFE OF SWEET BREAD MADE BY SUBTITUTION OF WHEAT FLOUR WITH LOKAL SAGO STARCH - Usman Pato; Akhyar Ali; Evi Sribudiani; Dewi Librianti; Mukmin ' (Jurnal Sagu, 2013)
The demand of Indonesia for wheat flour is predicted to increase by at least 6% every year. Meanwhile,Indonesia especially Riau Province has many kinds of food recourse viz. sago starch. The objective of thisstudy was to find out the best formulation in production of sweet bread made from wheat flour substitutedwith sago flour. Experimental study was conducted in Completely Randomized Design with six treatmentsand each treatment was done in three replications. Parameters observed were the contents of moisture, ash,and starch as well as leavening power, self life and organoleptic assessment of sweet bread. The dataobtained were analyzed by ANOVA and was continued with DNMRT test at 5% level. The organoleptic datawere analyzed by Friedman Test and data of gelatinous filament, flavor and rancidity were presented bydescriptive analysis. Results showed that substitution of wheat flour with sago starch significantly influencedmoisture and starch contents, leavening power and the organoleptic properties of sweet bread. However,substitution of sago starch did not affect ash content of sweet bread. In general, substitution up to 50% ofsago starch had met the Indonesian quality standard of sweet bread (SNI 01-3840-1995) except for lowleavening power. In addition, the self life of sweet bread in the treatment TM5 (wheat flour 50% and 50%sago starch) was similar to that of commercial sweet bread.Key words: sweet bread, sago starch, quality, self life